Kinetics of α-cordierite formation from nano-oxide powders. Issue 16 (15th August 2022) - Saheb, N.; Lamara, S.; Sahnoune, F.; Hassan, S.F.
Abstract: This work reports, for the first time, the kinetics of α-cordierite (Mg2 Al4 Si5 O18 ) formation from Al2 O3, SiO2, and MgO nano-oxide powders. Isothermal and non-isothermal kinetic analysis was performed by Differential Thermal Analysis (DTA) and thermodilatometric analysis (TDA). The thermal measurements were performed at high heating rates (20–70 °C/min) for DTA and low rates (3–9 °C/min) for TDA. Phase transformations leading to the formation of α-cordierite were characterized by x-ray diffraction (XRD). The Kissinger, Boswell, and Ozawa methods were used to calculate the activation energy. The Avrami parameter ( n ) and dimensionality of crystal growth ( m ) were calculated using the Augis–Bennett and Matusita equations, respectively. Analysis of samples heated in the DTA equipment or the dilatometer confirmed that the reaction of MgO, Al2 O3, and SiO2 led to the formation of enstatite, cristobalite, and metastable μ-cordierite. The later transformed to stable α-cordierite. The activation energy calculated by both isothermal and non-isothermal treatments is 633 and 667 kJ/mol, respectively, for DTA; and is 544 and 646 kJ/mol, respectively, for TDA. The growth morphology parameters n and m, obtained from isothermal and non-isothermal DTA treatments, are both close to 2 indicating that bulk nucleation with constant number of nuclei is dominant in α-cordierite crystallization followed by two-dimensional growth of α-cordierite crystals with plate-like morphology controlled by interface reaction. While those obtained from isothermal and non-isothermal TDA treatments, are both about 1.5 indicating that bulk nucleation is dominant in α-cordierite crystallization followed by three-dimensional growth of α-cordierite crystals with polyhedron-like morphology controlled by diffusion from a constant number of nuclei. A low coefficient of thermal expansion (CTE) of 0.9 × 10 −6 /°C was measured, in the range 200–1350 °C, for a sample sintered at 1400 °C‏ for 2 h.